2021
DOI: 10.3389/fimmu.2021.686273
|View full text |Cite
|
Sign up to set email alerts
|

CD27-CD38lowCD21low B-Cells Are Increased in Axial Spondyloarthritis

Abstract: B-cells have received little attention in axial spondyloarthritis (axSpA) and for this reason their role in pathogenesis remains unclear. However, there are indications that B-cells may be involved in the disease process. Our objective was to obtain insights into the composition of the peripheral B-cell compartment of axSpA patients compared to healthy donors (HD) and patients with primary Sjögren’s syndrome (pSS), a typical B-cell-associated autoimmune disease. Special emphasis was given to CD27-negative B-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…In particular, plasmablasts (and plasma cells) express high levels of CD38, along with high levels of CD27 [59]. In AS patients, the majority of studies (four out of six), including our own, revealed increased frequencies of circulating plasmablasts (CD27 hi /CD38 hi cells) [20,38,46]. Thus, phenotypical analysis of circulating B cells in AS provided some evidence that there are more activated B cells and plasma cells, compared to in healthy individuals.…”
Section: Activated B Cells In Asmentioning
confidence: 48%
See 4 more Smart Citations
“…In particular, plasmablasts (and plasma cells) express high levels of CD38, along with high levels of CD27 [59]. In AS patients, the majority of studies (four out of six), including our own, revealed increased frequencies of circulating plasmablasts (CD27 hi /CD38 hi cells) [20,38,46]. Thus, phenotypical analysis of circulating B cells in AS provided some evidence that there are more activated B cells and plasma cells, compared to in healthy individuals.…”
Section: Activated B Cells In Asmentioning
confidence: 48%
“…Similar to T cells, the expression of CXCR3 on B cells is also regulated by T-bet [34]. We have shown in AS patients that amongst CD21 low B cells (see following section), the frequency of CXCR3 + B cells is indeed strongly associated with the frequency of T-bet + B cells [20]. T-bet + B cells are postulated to represent germinal center-derived B cells destined to become antibody secreting cells [33].…”
Section: Gene Variants In As Modulating B Cell Functionmentioning
confidence: 93%
See 3 more Smart Citations